Neuraminidase-3 Is a Negative Regulator of LFA-1 Adhesion - Howlader, Md. Amran; Li, Caishun; Zou, Chunxia; Chakraberty, Radhika; Ebesoh, Njuacha; Cairo, Christopher W. (Frontiers in Chemistry, 2019)
Within the plasma membrane environment, glycoconjugate-receptor interactions play an important role in the regulation of cell-cell interactions. We have investigated the mechanism and activity of the human neuraminidase (NEU) isoenzyme, NEU3, on T cell adhesion receptors. The enzyme is known to prefer glycolipid substrates, and we confirmed that exogenous enzyme altered the glycolipid composition of cells. NEU3 was able to modify the sialic acid content of purified LFA-1 in vitro. Enzymatic activity of NEU3 resulted in re-organization of LFA-1 into large clusters on the membrane. This change was facilitated by an increase in the lateral mobility of LFA-1 upon NEU3 treatment. Changes to the lateral mobility of LFA-1 were specific for NEU3 activity, and we observed no significant change in diffusion when cells were treated with a bacterial NEU (NanI). Furthermore, we found that NEU3 treatment of cells increased surface expression levels of LFA-1. We observed that NEU3-treated cells had suppressed LFA-1 adhesion to an ICAM-1 coated surface using an in vitro static adhesion assay. These results establish that NEU3 can modulate glycoconjugate composition and contribute to the regulation of integrin activity. We propose that NEU3 should be investigated to determine its role on LFA-1 within the inflammatory cascade.